The long-term consequences of the global 1918 influenza pandemic: A systematic analysis of 117 IPUMS international census data sets - Sebastian Vollmer; Juditha Wójcik (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2017)
Several country-level studies, including a prominent one for the United States, have identified long-term effects of in-utero exposure to the 1918 influenza pandemic (also known as the Spanish Flu) on economic outcomes in adulthood. In-utero conditions are theoretically linked to adult health and socioeconomic status through the fetal origins or Barker hypothesis. Historical exposure to the Spanish Flu provides a natural experiment to test this hypothesis. Although the Spanish Flu was a global phenomenon, with around 500 million people infected worldwide, there exists no comprehensive global study on its long-term economic effects. We attempt to close this gap by systematically analyzing 117 Census data sets provided by IPUMS International. We do not find consistent global long-term effects of influenza exposure on education, employment and disability outcomes. A series of robustness checks does not alter this conclusion. Our findings indicate that the existing evidence on long-term economic effects of the Spanish Flu is likely a consequence of publication bias.
Keywords: 330